ANALISIS KEBIJAKAN PENENTUAN KEBUTUHAN PENDIDIKAN DAN PELATIHAN PEGAWAI NEGERI SIPIL DI JAWA TIMUR - Samidi Samidi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2016)
Providing education and training of civil servants is always based on a system which is a series of 3 (three) stages, namely 1) determination of educational and training needs;2) the education and training; and3) evaluation of post education and training.The ineffectiveness of the implementation of policy determination of the needs of education and technical training as well as functional is affected by 4 (four) factors: a lack of effective communication, inadequate resources, disposition or necessary tendency of the parties concerned still needs to be improved and the bureaucratic structure of Board of Education and Training East Java Province who have not specified the task of identifying the needs of education and training into staff duties.Based on the results of the study as stated, so that the implementation of policy determination of the needs of education and technical training as well as functional can achieve maximum results compared with the current, then the determination of need for education and training would need to be addressed more effectively based on needs analysis and any organization providing education and technical and functional training should be based on educational needs and appropriate training. Model analysis of the corresponding need at the moment is T-NAT that can be tested and adapted to conditions of Board of Education and Training of East Java province at this time.